Evaluating enhanced pulse oximetry auditory displays for neonatal oxygen targeting: A randomized laboratory trial with clinicians and non-clinicians. (February 2023) - Hinckfuss, Kelly; Sanderson, Penelope M.; Brecknell, Birgit; Loeb, Robert G.; Liu, David; Liley, Helen
Abstract: Standard pulse oximeter auditory tones do not clearly indicate departures from the target range of oxygen saturation (SpO2 ) of 90%–95% in preterm neonates. We tested whether acoustically enhanced tones would improve participants' ability to identify SpO2 range. Twenty-one clinicians and 23 non-clinicians used (1) standard pulse oximetry variable-pitch tones plus alarms; (2) beacon-enhanced tones without alarms in which reference tones were inserted before standard pulse tones when SpO2 was outside target range; and (3) tremolo-enhanced tones without alarms in which pulse tones were modified with tremolo when SpO2 was outside target range. For clinicians, range identification accuracies (mean (SD)) in the standard, beacon, and tremolo conditions were 52% (16%), 73% (14%) and 76% (13%) respectively, and for non-clinicians 49% (16%), 76% (13%) and 72% (14%) respectively, with enhanced conditions always significantly more accurate than standard. Acoustic enhancements to pulse oximetry clearly indicate departures from preterm neonates' target SpO2 range. Highlights: The oxygen saturation of premature neonates receiving oxygen must be kept in a target range, lower than that of adults. We tested clinicians' and non-clinicians' ability to identify neonate oxygen saturation range from pulse oximeter sounds. Acoustic enhancements to the pulse oximeter sound improved participants' ability to identify oxygen saturation range. Acoustic enhancements also generally improved participants' ability to detect when oxygen saturation left the target range. The enhancements to the pulse oximetry sound could help clinicians more effectively timeshare monitoring with visual tasks.